DETECTION AND IMPLEMENTATION OF ALTERNATE DATA STREAMS IN THE COMPUTER AND NETWORK SYSTEMS: DETECTION AND IMPLEMENTATION OF ALTERNATE DATA STREAMS IN THE COMPUTER AND NETWORK SYSTEMS - Boyanov, Petar (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
In this paper a common detectionand implementation of Alternate Data Streams in the operating system Windows Server 2008 R2 is made. Nowadays it is very important each system administrator and security professional to detect and analyze different types of alternate data streams. These steams can hide sensible secret or malicious files that can damage some of the computer and networks resources.